A pilot service-evaluation examining change in HbA1c related to the prescription of internet-based education films for type 2 diabetes. Issue 3 (June 2017) - Rice, S.; Cranch, H.; Littlemore, K.; Mortimer, J.; Platts, J.; Stephens, J.W.
Highlights: The uptake of prescribed films was 28%. Film watching was associated with a mean difference in HbA1c of −9.0 mmol/mol. Film prescribing may be used to facilitate and encourage structured education. This study should encourage research of internet-educational tools in diabetes. Abstract: We undertook a pilot service-evaluation of prescribed internet-based patient education films for patients with type 2 diabetes. The uptake was 28% and film watching was associated with a relative mean difference in HbA1c of −9.0 mmol/mol in the film watchers compared to non-watchers over a three-month period (P = 0.0008).